Metabolic profile during pregnancy in BRISA birth cohorts of Ribeirão Preto and São Luís, Brazil - Rodrigues,I.C. (2021)
During pregnancy, metabolic changes that develop in women may increase the risk of diseases and conditions that may also harm the life of the growing fetus. The aim of the present study was to identify and compare the metabolic profile (MP) during pregnancy in two birth cohorts in 2010 in the cities of Ribeirão Preto (RP) and São Luís (SL), Brazil. Pregnant women (1393 in RP and 1413 in SL) were studied; information was obtained through questionnaires in addition to anthropometric, biochemical, and blood pressure measurements. Data are presented as means and proportions. To compare the characteristics of pregnant women in both cities, chi-squared and Student's t-tests were applied, with 5% significance level. Ribeirão Preto presented higher mean values than SL for pre-gestational body mass index (24.5 vs 23 kg/m2, P<0.001), systolic (108.4 vs 102.8 mmHg, P<0.001) and diastolic (65.9 vs 61.8 mmHg, P<0.001) blood pressure, total cholesterol (226.3 vs 213.7 mg/dL, P<0.001) and fractions, and glycemia (84.5 vs 80.2 mg/dL, P<0.001), except for triglycerides (P=0.135). Women from RP also showed higher rates of pre-gestational overweight and obesity compared with SL (40.1 vs 25.8%). In the present study, pregnant women in RP had a worse gestational metabolic profile than those in SL, with higher pre-gestational excess weight, indicating that nutritional transition was more advanced in the more developed city.